THE IMPACT OF INNOVATION ON THE POLICY OF AN INDONESIAN FOOD COMPANY THROUGH OPERATIONAL RESEARCH - Nurhayati, Nurhayati (Institute of Computer Science (IOCS), 2023)
This paper examines the impact of innovation on policy formulation in Indonesian food industries and the significance of operational research in this particular setting. The systematic literature study demonstrates that firm policies have been considerably transformed by breakthroughs in product development, technology, and business models. The efficiency and effectiveness of these policy adjustments can be enhanced by utilizing operational research approaches such as mathematical modeling or simulation. The study highlights the influence of particular contextual elements, such as regulatory frameworks and customer preferences in Indonesia, on the dynamics of innovation-policy. Nevertheless, it highlights a research void caused by a dearth of empirical investigations that explore this correlation through operational research in Indonesian food industries. The article provides a comprehensive summary of current knowledge, emphasizing important topics such as digital transformation and sustainability, while also laying the groundwork for future research.